Exploration of Method for Slope Stabilization Influenced by Unsaturated Soil - Ishak, M.F.; Muhammad Farhan, Zolkepli (Publications International Lahore, Pakistan, 2017)
This study will lead to the analysis of unsaturated soil using Bishop’s Simplified method which is one method to analyze slope stability in method of slices. Bishop’s original formula of saturated soil was modified by adding the element of matric suction, ( ) a w   together with unsaturated friction angle,b  which is applicable for the analysis of unsaturated soil. In this study, 40 kPa of matric suctions was applied in the analysis for both Bishop and Fellenius methods. From the analysis, the results indicate that the factor of safety (FOS) value of Bishop’s Simplified method was 4.41 % higher than Fellenius’s method for 40 kPa suction, as the soil is in unsaturated condition. The reason for the relative accuracy of Bishop’s Simplified method is that in considering only the vertical equilibrium of any slice, there is no need to account for the horizontal components of the inter-slice forces.